The camp analogue, dbcAMP can stimulate rabbit reproductive functions: I. Effect on ovarian folliculogenesis, ovulation and embryo production - Chrenek P.; Pivko J.; Makarevich Av.; Kubovičová Helena; Balazi A.; Sirotkin Av. (Acta Veterinaria, 2012)
The aim of our study was to examine the influence of administration of N6,2’-dibutyryladenosine 3’5’-cyclic monophosphate (dbcAMP), a cAMP agonist, on ovarian folliculogenesis and atresia, as well as on reproductive efficiency in rabbits, whose ovarian cycle and ovulation was induced by gonadotropins. Ovarian cycle and ovulation of control rabbits were induced by 20 IU/kg PMSG followed by 35 IU/kg hCG administration. Experimental animals received PMSG and hCG together with dbcAMP (at 5, 25 or 50 μg/animal). After ovulation and insemination, the animals were sacrificed. Ovaries were weighted, histological sections of ovaries were prepared, and the presence of ovulated and not ovulated follicles and different stages of atresia was evaluated by light microscopy. The eggs were flushed from the oviducts after insemination and cultured up to blastocyst cell stage. Numbers of ovarian Corpora lutea, ovulated oocytes and oocyte-derived zygotes and embryos reaching hatched blastocyst stage were determined. Administration of dbcAMP (at doses 25 or 50 μg/animal, but not at 5 μg/animal) was able to increase the proportion of follicles with cystic and luteinization-related atresia. Furthermore, dbcAMP (50 μg/animal, but not lower doses) increased the ovarian mass, number of Corpora lutea, number of harvested oocytes, zygotes and embryos at blastocyst stage derived from these zygotes after culture. These data demonstrate that dbcAMP can stimulate rabbit ovarian follicle atresia, ovulation, oocyte, zygote and embryo yield and development. Furthermore, they confirm in the involvement of cyclic nucleotide-dependent intracellular mechanisms in the control of rabbit reproductive functions and potential practical usefulness of dbcAMP in improving animal reproduction and fertility.